PENGARUH LIKUIDITAS, LEVERGE, DAN AKTIVITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - B31109033, Muhammad Yunus (Jurnal Manajemen Update, 2016)
The purpose of this research is analyzing the influence of liquidity (current ratio), leverage (debt ratio), and activities (total assets turnover) to profitability, either partially in food and drink companies listed in Indonesia Stock Exchange during 2009-2014. The method of analysis used is multiple linear regression analysis. Result of regression analysis performed after the model was not experiencing classic symptoms such as normality, multicollinerity, autocorrelation, and heteroscedasicity. Testing statistical test is carried out with a multiple linear regression. The samples were 72 food and drink companies listed in Indonesia Stock Exchange. Samples were 72 food and beverage companies listed in Indonesia Stock Exchange during the years 2009-2014 Results of testing hypotheses F test showed that the level of significance F is smaller than the significance level (0.000 <0.05), then the variable liquidity (current ratio), leverage (debt ratio), and activities (total asset turnover) simultaneously affect the profitability (return on equity). Results of hypothesis testing t test showed a significance level of t for variable liquidity (current ratio) is 0.010. While the level of significance of t for variable leverage (debt ratio), and activities (total asset turnover) was 0,016 and 0,000. Of the three levels above the significant value t is smaller than the significance level (0.05), then the variable liquidity (current ratio), leverage (debt ratio), and activities (total asset turnover) partially affect the profitability. While variable the dominant influence on the profitability of activities is variable (total asset turnover). Â  Keywords : current ratio, debtÂ  ratio, total assets turnover, return on equity